2002
DOI: 10.1136/gut.50.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Histogenesis of human colorectal adenomas and hyperplastic polyps: the role of cell proliferation and crypt fission

Abstract: Background: The histogenesis of human colorectal hyperplastic polyps and colorectal adenomas is poorly understood even now. Method: Human colorectal adenomas, hyperplastic polyps, and normal colorectal mucosae (patients with familial adenomatous polyposis and hereditary non-polyposis colorectal carcinoma were excluded) were obtained during colonoscopy and microdissected into individual crypts. Morphology, cell proliferation characteristics, and fission indices of crypts isolated from these lesions were then st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
137
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(152 citation statements)
references
References 36 publications
14
137
0
1
Order By: Relevance
“…Crypt expansion in colon cancer and polyposis can be caused by 'bottom-up' crypt fission (division of an existing crypt starting at its base), or by 'top-down' de novo crypt formation (budding of a new crypt from a crypt or villus) 9,10,[30][31][32][33] . We found that both mechanisms of crypt expansion occurred in PTEN-deficient intestines and were associated with an excessive production of M + ISC/p cells ( Fig.…”
Section: Musashi + Stem and Progenitor Cells Initiate Polyp Formationmentioning
confidence: 99%
“…Crypt expansion in colon cancer and polyposis can be caused by 'bottom-up' crypt fission (division of an existing crypt starting at its base), or by 'top-down' de novo crypt formation (budding of a new crypt from a crypt or villus) 9,10,[30][31][32][33] . We found that both mechanisms of crypt expansion occurred in PTEN-deficient intestines and were associated with an excessive production of M + ISC/p cells ( Fig.…”
Section: Musashi + Stem and Progenitor Cells Initiate Polyp Formationmentioning
confidence: 99%
“…Previous studies in the developing brain and inner ear of Math1 knockout mice have shown that cerebellar granule neurons and inner ear hair cells of mice fail to differentiate, respectively (Bermingham et al, 1999;Gazit et al, 2004;Fritzsch et al, 2005;Jones et al, 2006 (Zheng et al, 2000;Shou et al, 2003;Kawamoto et al, 2003). More importantly, targeted deletion of Math1 also resulted mice intestinal secretory cells, including goblet cells, in failure of differentiate (Yang et al, 2001) and Hath1 can induce Muc2 expression (van de Wetering et al, 2002). However, a potential role for Hath1 in colon cancer is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of human colon carcinogenesis, Muc2 expression has decreased while the numbers of goblet cells reduced (Hamilton, 1992;Hanski et al, 1997). The majority of colon carcinomas produce a little mucin except for mucinous adenocarcinoma and signet-ring cell carcinoma (Hanski et al, 1997;Wong et al, 2002). Some studies have shown that Muc2 was concerned with colon tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Within adenomas and hyperplastic polyps it is observed that crypts are elongated and deformed, exhibiting budding and multiple fission events (Araki et al, 1995;Brittan and Wright, 2004;Wong et al, 2002). (Although crypt fission is a normal process in the human colon the rate of crypt division in adenomas is significantly raised).…”
Section: Introductionmentioning
confidence: 99%